Penggunaan Media Pembelajaran Assembler Edu untuk Meningkatkan Hasil Belajar IPA Siswa Sekolah Menengah Pertama - Evriza, Dita Lestari (Jurnal Didaktika Pendidikan Dasar, 2025)
This action research aims to improve the learning outcomes of class VIII students at SMPN 5 Singingi Hilir used Assemblr Edu. This research is classroom action research carried out in two cycles. Data collection methods use interviews, observation and tests. The results of the research show an increase in student learning outcomes in the human movement sistem material. In cycle II, teacher observation results increased from 70.5% (fair) to 84.7% (good) and student observation results also increased from 62% (poor) to 82% (good). Student learning outcomes in cycle I obtained an average of 66.7 (poor) rising to 82.5 (Good). N-Gain in cycle I 0.3 (medium) and in cycle II 0,4 (medium). Based on the results of the study, it shows that the Assembler Edu learning media can improve the science learning outcomes of students at Smpn 5 Singingi Hilir.